Smartphones and the Learning of French as a Foreign Language in the Public Universities in Kenya - Wasike, Stella; Kazadi , Muteba; Auma , Rose (Journal of English Language Teaching and Applied Linguistics, 2021)
The use of ICT in education has become increasingly important in the education systems of both developed and developing countries. ICT as a course has been introduced in the university programmes. Several researchers have identified a Smartphone as a promising form of ICT in education systems which can revolutionalize career formations. However, there is need for a profound reflection on its possible use in the learning of French as a foreign language in the public universities. This study explored the use of a Smartphone in the learning of French as a foreign language by undergraduate students of the public universities in Kenya. The study focused on the following objectives: First, it assessed the use of a Smartphone in the learning process of French as a foreign language by undergraduate students in universities in Kenya. Secondly, it established when undergraduate students turn to the use of Smartphones in the learning of French as a foreign language. Lastly, it evaluated if the frequent use of a Smartphone by undergraduate students of the public universities in Kenya, adds value to their oral and written linguistic competence. The new knowledge derived from this study would enhance and contribute to new learning techniques of French in the context of the use of a Smartphone. This knowledge would also guide on how this device can be integrated in the learning of French as a foreign language.